2022
DOI: 10.1002/jlb.1a0422-211r
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg1 ameliorates sepsis-induced acute kidney injury by inhibiting ferroptosis in renal tubular epithelial cells

Abstract: Acute kidney injury (AKI) represents a prevailing complication of sepsis, and its onset involves ferroptosis. Ginsenoside Rg1 exerts a positive effect on kidney diseases. This study explored the action of ginsenoside Rg1 in sepsis‐induced AKI (SI‐AKI) by regulating ferroptosis in renal tubular epithelial cells (TECs). Sepsis rat models were established using cecal ligation and puncture (CLP) and cell models were established by treating human renal TECs (HK‐2) with LPS to induce ferroptosis. Serum creatinine (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…Previous studies have shown that resveratrol protects against cisplatin-induced acute kidney injury by improving MDA, GSH, and endogenous antioxidant enzyme activity and improving the in vivo metabolism of cisplatin ( Darwish et al, 2018 ; Ibrahim et al, 2018 ). Guo et al found that ginsenoside Rg1 inhibited ferroptosis by reducing iron accumulation and inhibiting lipid peroxidation ( Guo et al, 2022 ). In the present study, we demonstrated that RFP could effectively reduce lipid peroxidation production while increasing the level of the antioxidant enzyme GSH in a cisplatin-induced mouse model of acute kidney injury, suggesting that RFP could alleviate cisplatin-induced oxidative damage induced by acute kidney injury.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that resveratrol protects against cisplatin-induced acute kidney injury by improving MDA, GSH, and endogenous antioxidant enzyme activity and improving the in vivo metabolism of cisplatin ( Darwish et al, 2018 ; Ibrahim et al, 2018 ). Guo et al found that ginsenoside Rg1 inhibited ferroptosis by reducing iron accumulation and inhibiting lipid peroxidation ( Guo et al, 2022 ). In the present study, we demonstrated that RFP could effectively reduce lipid peroxidation production while increasing the level of the antioxidant enzyme GSH in a cisplatin-induced mouse model of acute kidney injury, suggesting that RFP could alleviate cisplatin-induced oxidative damage induced by acute kidney injury.…”
Section: Resultsmentioning
confidence: 99%
“…3,4 It has been demonstrated that the pathogenesis of sepsis-induced AKI is closely associated with inflammatory response, apoptosis, oxidative stress, and ferroptosis. [6][7][8] CHAC1 is identified as a mammalian pro-apoptotic factor, 13 which may be involved in apoptosis, oxidative stress, and ferroptosis. In the present study, the level of CHAC1 was found to be up-regulated in the kidney tissues of mice with sepsisinduced MODS according to bioinformatic analysis.…”
Section: Discussionmentioning
confidence: 99%
“…35 In addition, the study conducted by Guo et al revealed that ginsenoside Rg1, belonging to the class of steroid glycosides, suppressed ferroptosis to improve sepsis-induced AKI. 6 Moreover, ferroptosis was involved in LPS-induced AKI through mitochondria-derived ROS. 36 In this study, our results also demonstrated that LPS treatment enhanced cell apoptosis, oxidative stress, and ferroptosis in HK-2 cells that were notably attenuated by the knockdown of CHAC1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another small molecule, ginsenoside Rg1, can improve the viability of HK-2 cells and reduce the accumulation of iron and lipid peroxidation. Its anti-ferroptosis activity is dependent on FSP1 ( Guo et al, 2022 ).…”
Section: Ferroptosis In Different Types Of Acute Kidney Injurymentioning
confidence: 99%